Papillary renal cell carcinoma embedded in an oncocytoma: Case report of a rare combined tumour of the kidney - Sejben, István; Szabó, Zoltán; Loránd, Márta; Sükösd, Farkas; Cserni, Gábor (Canadian Urological Association Journal, 2013)
An asymptomatic 1-cm large papillary renal cell carcinoma (RCC) embedded in a 3.5-cm large oncocytoma was diagnosed and removed by right nephrectomy in a 68-year-old male investigated for the abdominal symptoms associated with cholelithiasis. The papillary RCC displayed positive immunohistochemical stainings with cytokeratin 7, alpha-methylacyl-CoA racemase and vimentin and was negative for the E-cadherin and CD117 immunostains, whereas the oncocytoma part showed opposite staining patterns. No gains of chromosomes 7 and 17 or loss of chromosome Y was detected in the papillary carcinoma by fluorescent in situ hybridization with centromeric enumeration probes. This finding is in keeping with the morphologic diagnosis of type 2 papillary RCC reported to have lower rates of these characteristic chromosomal changes. The combination of papillary RCC and oncocytoma, two tumours of different postulated origin, is extremely rare. It may represent a simple coincidence, but 2 previous cases and our current one share a few features, including the intimate embedment of the papillary RCC in the oncocytoma, the small size of the RCC and the old age of the patients. This case raises the point that renal oncocytomas can contain a hidden malignant tumour.